Peaceful settlement as a means of preventing tax: An applied research in the General Commission for Taxation evasion (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The reconciliation of tax reconciliation is one of the legal methods used by the financial authority in Iraq, which is done with the taxpayerThe research dealt with the weakness of tax revenues for many reasons, including tax evasion, which led to the search for ways to reduce evasion to increase the tax revenue, and settlement reconciliation one of these means .The research proceeded from the premise that the use of a more broadly settled settlement would govern the tax evasion of taxpayers.The researchers used a series of studies and previous research, books and other sources related to the subject of research, and this was done through the theoretical framework, and the practical aspect that included the financial statements.The most important results were:The settlement of the settlement enhances the application of the principle of tax compliance, and leads to the payment of the tax evaded payment plus the fine imposed on him and this leads to an increase in tax revenues, and also lead to the detection of the taxpayer evaded real financial statements, which will be taken as a basis for accounting for the years later also this Leading to a reduction in tax evasion.The main conclusions reached were:1-The system used in the settlement of reconciliation in its traditional form (the powers distributed between the branches and the General Authority for Taxation and the Ministry of Finance), and did not provide a new step to become wider as is the US compliance law.